Knowledge, attitudes and other factors associated with assessment of tobacco smoking among pregnant Aboriginal women by health care providers: a cross-sectional survey - Passey Megan E; D'Este Catherine A; Sanson-Fisher Robert W (BMC, 2012)
Abstract Background As with many Indigenous peoples, smoking rates among Aboriginal Australians are considerably higher than those of the non-Indigenous population. Approximately 50% of Indigenous women smoke during pregnancy, a time when women are more motivated to quit. Antenatal care providers are potentially important change agents for reducing the harms associated with smoking, yet little is known about their knowledge, attitudes or skills, or the factors associated with providing smoking cessation advice. Methods This paper aimed to explore the knowledge and attitudes of health care providers caring for pregnant Australian Aboriginal women with regard to smoking risks and cessation; and to identify factors associated with self-reported assessment of smoking. A cross-sectional survey was undertaken with 127 staff providing antenatal care to Aboriginal women from two jurisdictions: the Northern Territory and New South Wales, Australia. Measures included respondents' estimate of the prevalence of smoking among pregnant women; optimal and actual assessment of smoking status; knowledge of risks associated with antenatal smoking; knowledge of smoking cessation; attitudes to providing cessation advice to pregnant women; and perceived barriers and motivators for cessation for pregnant women. Results The median provider estimate of the smoking prevalence was 69% (95%CI: 60,70). The majority of respondents considered assessment of smoking status to be integral to antenatal care and a professional responsibility. Most (79%) indicated that they assess smoking status in 100% of clients. Knowledge of risks was generally good, but knowledge of cessation was poor. Factors independently associated with assessing smoking status among all women were: employer service type (p = 0.025); cessation knowledge score (p = 0.011); and disagreeing with the statement that giving advice is not worth it given the low level of success (p = 0.011). Conclusions Addressing knowledge of smoking risks and cessation counselling is a priority and should improve both confidence and ability, and increase the frequency and effectiveness of counselling. The health system must provide supports to providers through appropriate policy and resourcing, to enable them to address this issue.